Malaria survey data and geospatial suitability mapping for understanding spatial and temporal variations of risk across Kenya - Caroline Kioko; Justine Blanford (Parasite Epidemiology and Control)
Malaria remains a public health concern in Kenya where children and pregnant women are vulnerable groups. The common interventions in place to fight malaria include using insecticide-treated bed nets (ITNs), knowledge and awareness about malaria, and intake of malaria anti-malaria drugs. Despite the availability of these interventions, Kenya still records more than 10,000 clinical cases annually. In this study, we examined how malaria and interventions varied across Kenya for 2015 and 2020. We analyzed the Kenya Malaria Indicator Survey (N = 10,072) for 2015 and, (N = 11,549) for 2020, and climate data with Fuzzy overlay method to examine how malaria and its interventions relate to environmental conditions required for malaria. The study found that 79 % of malaria cases were distributed in lake endemic, 11 % in coastal endemic, 7 % in highland epidemic, and 3 % in seasonal zone. Use of Insecticide-treated bed nets (ITNs) was 77 % in lake endemic, 13 % in coastal endemic, 9 % in highland epidemic, and 1 % in seasonal zone. Knowledge about malaria was 82 % in lake endemic, 9 % in highland epidemic, 6 % in coastal endemic, and 3 % in seasonal zone. Additionally, based on climate data, lake endemic zone was 94 % suitable for malaria transmission compared to other zones. Despite the use of ITNs and awareness about malaria, malaria transmission continues to be a threat especially in counties in the lake endemic zone. Furthermore, place of residence, climate factors, ownership of ITNs may be associated with malaria in the region.